Hydrogel films and microcapsules based on soy protein isolate combined with alginate. Issue 4 (23rd September 2016) - Tansaz, Samira; Durmann, Ann‐Katrin; Detsch, Rainer; Boccaccini, Aldo R.
ABSTRACT: Alginate hydrogels are combined with soy protein isolate (SPI), a plant derived protein with low immunogenicity, appropriate biodegradability and low cost, to produce biocompatible films, and microcapsules. The cell–material interaction is assessed through the use of mouse embryotic fibroblast cells (MEF cells) on films, and the results illustrate that the alginate/SPI hydrogel films support cell attachment, spreading, and proliferation. Cell biology results combined with degradation studies suggest that such hydrogels are promising biomaterials for soft tissue regeneration or as wound dressing materials. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 44358. Abstract :